Neonatal Hyperbilirubinemia in a Marginalized Population on the Thai-Myanmar Border: a study protocol. - Thielemans, L; Trip-Hoving, M; Bancone, G; Turner, C; Simpson, J; Hanboonkunupakarn, B; van Hensbroek, M; van Rheenen, P; Paw, M; Nosten, F; McGready, R; Carrara, V (BioMed Central, 2017)
BACKGROUND: This study aims to identify risk factors and the neurodevelopmental impact of neonatal hyperbilirubinemia in a limited-resource setting among a refugee and migrant population residing along the Thai-Myanmar border, an area with a high prevalence of glucose-6-phosphate dehydrogenase-deficiency. METHODS: This is an analytic, observational, prospective birth cohort study including all infants of estimated gestational age equal to or greater than 28 weeks from mothers who followed antenatal care in the Shoklo Malaria Research Unit clinics. At birth, a series of clinical exams and laboratory investigations on cord blood will be carried out. Serum bilirubin will be measured in all infants during their first week of life. All the infants of the cohort will be clinically followed until the age of one year, including monitoring of their neurodevelopment. DISCUSSION: The strength of this study is the prospective cohort design. It will allow us to collect information about the pregnancy and detect all infants with neonatal hyperbilirubinemia, to observe their clinical response under treatment and to compare their neurodevelopment with infants who did not develop neonatal hyperbilirubinemia. Our study design has some limitations in particular the generalizability of our findings will be limited to infants born after the gestational age of 28 weeks onwards and neurodevelopment to the end of the first year of life. TRIAL REGISTRATION: ClinicalTrials.gov ID NCT02361788 , registration date September 1st, 2014.